PENGARUH KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG BANDAR JAYA PROVINSI LAMPUNG - Nanda Nur Rizky; Afdal Mazni; Suharto Suharto (SIMPLEX: Journal of Economic Management, 2021)
Job satisfaction is related to people's evaluation of their work on issues that are important to them. The purpose of this study was conducted to determine the job satisfaction of employees at PT. Bank Syariah Mandiri Branch Office Bandar Jaya Lampung Province by using communication and work motivation. The sample in this study was 32 respondents using Accidental Sampling. Data analysis was performed using Multiple Linear Regression Analysis through the SPSS version 21 program. The analysis shows that there is communication that affects job satisfaction, work motivation that affects job satisfaction, and communication with work motivation jointly affects job satisfaction